DIAGNOSIS OF ENDOCRINE DISEASE: IgG4-related thyroid autoimmune disease. Issue 5 (May 2019) - Rotondi, Mario; Carbone, Andrea; Coperchini, Francesca; Fonte, Rodolfo; Chiovato, Luca
Abstract : IgG4-related disease (IgG4-RD) is fibro-inflammatory, immune-mediated, systemic disease recognized as a defined clinical condition only in 2001. The prevalence of IgG4-RD is 6/100 000, but it is likely to be underestimated due to insufficient awareness of the disease. The diagnostic approach is complex because of the heterogeneity of clinical presentation and because of rather variable diagnostic criteria. Indeed, high concentrations of IgG4 in tissue and serum are not a reliable diagnostic marker. The spectrum of IgG4-RD also includes well-known thyroid diseases including Riedel's thyroiditis, Hashimoto's thyroiditis and its fibrotic variant, Graves' disease and Graves' orbitopathy. Results from clinical studies indicate that a small subset of patients with the above-mentioned thyroid conditions present some features suggestive for IgG4-RD. However, according to more recent views, the use of the term thyroid disease with an elevation of IgG4 rather than IgG4-related thyroid diseases would appear more appropriate. Nevertheless, the occurrence of high IgG4 levels in patients with thyroid disease is relevant due to peculiarities of their clinical course.